Intravenous lipo-prostaglandin E1 administration for patients with acute central retinal artery occlusion. Issue 1 (25th May 2022) - Suzuki, Takafumi; Obata, Ryo; Inoue, Tatsuya; Ueta, Yoshiki; Azuma, Keiko; Tate, Hideo; Kitamoto, Kohdai; Otaki, Chisato; Hashimoto, Yoshihiro; Aihara, Makoto; Tachi, Naoko
Abstract : Objective: This study aimed to investigate the anatomical and functional changes in patients with central retinal artery occlusion (CRAO) (n=21) treated with 10 µg/day intravenous liposomal prostaglandin E1 (lipo-PGE1). Methods and analysis: We used best-corrected visual acuity (BCVA), central retinal thickness with spectral domain optical coherence photography, optical intensity ratio (OIR) with imageJ software and retinal vessel diameter with fundus photography as indicators. Data were analysed using Tukey's multiple comparisons, Wilcoxon test or Spearman's correlation analysis as appropriate. Results: BCVA was significantly improved at 1 month and 3 months after the initial visit (from 2.18±0.60 to 1.54±0.84 and 1.53±0.88, p=0.030 and p=0.027, respectively). The ratio of retinal vein diameter to optic disc diameter increased in the first month (from 0.40%±0.13% to 0.52%±0.16%, p=0.005). In addition, the OIR at the initial visit was significantly correlated with BCVA at 3 months (p=0.006, r=0.58). No severe adverse effects were observed. Conclusion: The results showed that visual acuity and retinal vein constriction improved after lipo-PGE1 therapy. In addition, the OIR in the initial phase can be an indicator of visual prognosis after treatment with PGE1 in patients with CRAO.